2019
DOI: 10.1177/0954409719880770
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the crashworthiness design and collision dynamics of a subway train

Abstract: In this study, the crashworthiness of a subway train was assessed by establishing a finite element model for the first three carriages of the train and the track using the Hypermesh software. By utilising the *MAT_HONEYCOMB material model, a honeycomb in an anti-climbing energy-absorbing device was simulated. Moreover, the process of a subway train – travelling at a speed of 25 km/h – colliding with another identical train in a stationary and non-braking state was simulated by employing the finite element anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It can meet the requirements for engineering design, and has been widely used in research on passive safety in train collisions. [4][5][6][7][8][9][10] In this study, a one-dimensional train collision multi-body dynamics model was established using "LS-DYNA" software, as shown in Figure 4(a). The vehicle models were simulated using hexahedral solid elements with material #MAT 20, and only the translational degree of freedom in trains moving direction were retained, and other degrees of freedom were constrained.…”
Section: Dynamics Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It can meet the requirements for engineering design, and has been widely used in research on passive safety in train collisions. [4][5][6][7][8][9][10] In this study, a one-dimensional train collision multi-body dynamics model was established using "LS-DYNA" software, as shown in Figure 4(a). The vehicle models were simulated using hexahedral solid elements with material #MAT 20, and only the translational degree of freedom in trains moving direction were retained, and other degrees of freedom were constrained.…”
Section: Dynamics Model Establishmentmentioning
confidence: 99%
“…3 These simulation analyses often incorporate a finite element method and/or system dynamics method. Xie et al 4 set up a finite element model for the first three carriages of a subway train, and accessed the train's crashworthiness. Zhu et al 5 created a finite element model for a rigid barrier impacting a single vehicle, and proposed an energy absorption ratio for the vehicle body and its key components.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of train collision, Li et al [8] found that the time to achieve collision avoidance is constrained by the timing of events, such as wireless communication latency, driver reaction, safety protection distance, and deceleration rate. Xie et al [9] used HyperMesh software to establish the finite element model of the first three carriages and tracks of a train to evaluate the crashworthiness of a subway train. The energy absorption research of an anti-climbing energy absorption device under static compression and the collision analysis of the whole train are carried out.…”
Section: Introductionmentioning
confidence: 99%